Ethics, computing, and medicine : informatics and the transformation of health care - Goodman, Kenneth W., 1954- (Cambridge University Press, 1998)
New technology always raises compelling ethical questions. As those in medicine increasingly depend on computers and other intelligent machines, the intersection of ethics, computing and the health professions grows much more complex and significant. This book attempts systematically to identify and address the full range of ethical issues that arise when intelligent machines are used in medicine, nursing, psychology, and allied health professions. It maps and explores a variety of important issues and controversies, including ethics and evaluation in computational medicine, patient and provider confidentiality, responsibility for use of computers in medicine, appropriate use of decision support systems, outcomes of research and computational prognosis (including mortality predictions), and computer-based biomedical research - especially meta-analysis. This book is accessible to participants in the fields of bioethics and medical informatics. It is appropriate for physicians, nurses, administrators, ethicists, health attorneys, advanced undergraduates and graduate students.